SUPPORT OF IOT TECHNOLOGIES AND MOBILE CONTROL IN WAREHOUSES - Sobirov Anvarjon Muxammadjon o‘g‘li; Po‘latov Ziyohiddin Axunjon o‘g‘li (European Science Publishing, 2024)
Currently warehouse in the industry big changes happened is giving From places pulling inventories until storage, they whole supply chain efficiency in raising important role who plays efficient to tools turned.
Keywords: IoT, smart systems, artificial intelligence, AI, automated, inventory, control, encryption.